Mrs. Piper & the Society for Psychical Research - Sage, Michael, 1863-1931 (Salt Lake City, UT : Project Gutenberg, 2006)
"Mrs. Piper & the Society for Psychical Research" by Michael Sage is a historical account written in the early 20th century. This work closely examines the phenomena surrounding Mrs. Piper, a well-studied medium whose mediumship has been investigated by several members of the Society for Psychical Research. The book delves into the complexities and nuances of psychic phenomena, presenting detailed observations and lively discussions regarding the nature of mediumship, the role of skeptics, and the various theories that have attempted to explain her abilities. At the start of this account, the author introduces Mrs. Piper$1 (Bs remarkable mediumship, characterized by her ability to enter trance states and purportedly communicate with the deceased. The initial chapters outline the careful and rigorous investigations conducted by the Society's members, including Dr. Richard Hodgson and Professor William James, highlighting their skepticism towards fraud and their determination to understand the phenomenon. The narrative places emphasis on the struggle between scientific inquiry and spiritual understanding, laying the groundwork for further exploration into the often ambiguous nature of her messages and the identities of the controls that communicate through her, such as Phinuit and others. (This is an automatically generated summary.)s
Release date is 2006-09-25
E-text prepared by Stacy Brown, Suzanne Lybarger, and the Project Gutenberg Online Distributed Proofreading Team
Keywords: Spiritualism; Piper, Leonora, 1859-1950; Parapsychology -- Investigation -- Great Britain; Mediums -- Practice -- Great Britain